2023
DOI: 10.1186/s12872-022-02904-2
|View full text |Cite
|
Sign up to set email alerts
|

The psychological and behavioural factors associated with laypeople initiating CPR for out-of-hospital cardiac arrest: a systematic review

Abstract: Background Prompt, effective CPR greatly increases the chances of survival in out-of-hospital c ardiac arrest. However, it is often not provided, even by people who have previously undertaken training. Psychological and behavioural factors are likely to be important in relation to CPR initiation by lay-people but have not yet been systematically identified. Methods Aim: to identify the psychological and behavioural factors associated with CPR initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 130 publications
(222 reference statements)
0
8
0
Order By: Relevance
“…Instead of bystander CPR being a shared responsibility for a public rescue, it becomes the bystander's lone risk for helping the person experiencing the OHCA event. Previous studies have confirmed that risk perception lowered bystander's willingness to perform CPR, impacting their psychological stress and safety risk (Farquharson et al., 2023).…”
Section: Discussionmentioning
confidence: 86%
“…Instead of bystander CPR being a shared responsibility for a public rescue, it becomes the bystander's lone risk for helping the person experiencing the OHCA event. Previous studies have confirmed that risk perception lowered bystander's willingness to perform CPR, impacting their psychological stress and safety risk (Farquharson et al., 2023).…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, despite their inadequate knowledge, students had positive attitudes towards learning CPR ( 44 , 45 ). Those findings show that a positive attitude towards learning and performing CPR along with the perception of self-efficacy are essential determinants of people’s willingness to perform bystander BLS prior to arrival of professional help ( 46 , 47 ). Ensuring this readiness fulfills the 5th and 6th standards of the WHO Global Standards and Indicators for HPS ( 48 ), whereby the school expands its health-promoting resources to include teaching and non-teaching staff as well as parents (standard 5), and initiates new partnerships to contribute to the quality, sustainability, and impact of health promotion initiatives (standard 6).…”
Section: Discussionmentioning
confidence: 99%
“…Providing bystander CPR could be experienced as emotionally challenging and may cause uncertainty and concern that could prove difficult to face in daily life [ 18 ]. A recent systematic review [ 19 ] confirmed that psychological and behavioural factors had impact on the CPR initiation. It has also been shown that even if most VFRs consider their CPR to have been a positive experience and would resuscitate again, they experienced severe short-term psychological impacts [ 20 ].…”
Section: Introductionmentioning
confidence: 99%